The elusive welfare economics of price stability as a monetary policy objective: why New Keynesian central bankers should validate core inflation - Willem H. Buiter (European Central Bank (ECB), 2006)
The paper studies the inflation rate associated with optimal monetary and fiscal policy in a number of standard dynamic stochastic general equilibrium models with nominal price rigidities. While the focus is on Calvo-style nominal price contracts with a range of indexation rules for constrained price setters, the conclusions have much wider validity: (1) Regardless of whether nominal price and/or wage rigidities are due to New-Keynesian, Old-Keynesian or sticky-information Phillips curves, optimal inflation policy requires the validation, that is, the full accommodation of core producer inflation by actual producer price inflation;(2) Optimal monetary policy implements Bailey-Friedman optimal quantity of money rule. No welfare-economics based argument for price stability as an objective (let alone the overriding objective) of monetary policy can be established for the class of DSGE models with nominal rigidities for which they have been proposed by Woodford and others.
Keywords: E3; E4; E5; E6; 330; DSGE; inflation targeting; New Keynesian macroeconomics; Nominal price rigidities; Geldpolitik; Geldpolitisches Ziel; Preisstabilität; Regelbindung versus Diskretion; Theorie